Electrochemical Characterization of Chromate Free Conversion Coatings on Electrogalvanized Steel - Tomachuk, C. R. (2014)
The chromate conversion treatment is widely used, but it requires highly toxic chromic acid solutions with the consequent effluent disposal and ecological problems. The removal of these toxic chemicals is considered a priority within European Union. The corrosion resistance of three alternative treatments applied on electrogalvanised steel, and immersed in aerated 0.3 M Na2 SO4 solution, pH 10, at 25 °C, was investigated using electrochemical techniques. Their performance was compared with the obtained using the traditional Cr6+-based treatment in the same conditions. The achieved results show that the alternative coatings exhibited discrete protective properties in the sulphate solution. The nitro-cobalt chemical conversion treatment showed similar protective properties than the traditional Cr6+-based treatment, while with the Cr3+-based treatment those were very poor. The phosphate treatment initially performed acceptably but as the time elapsed, its protective properties decreased.